2012
DOI: 10.1111/j.1440-169x.2012.01335.x
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation of pre‐implantation embryos improves establishment of parthenogenetic stem cells and expression of imprinted genes

Abstract: Parthenogenetic embryonic stem cells (PgES) might advance cell replacement therapies and provide a valuable in vitro model system to study the genomic imprinting. However, the differential potential of PgES cells was limited. It could result from relative low heterology of PgES cells compared with ES cells from fertilization (fES), which produce different expression of most imprinted genes. Here, we described the establishment of PgES cells by aggregating parthenogenetic embryos at the 8-cell stage (aPgES cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 23 publications
3
22
1
Order By: Relevance
“…; Shan et al . ); however, we found using more embryos with small volume of medium in mircodrops was easier for manipulation and gave satisfactory results. In some trials we found that embryos began to cleave and form blastomeres as soon as culture conditions started (Fig.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…; Shan et al . ); however, we found using more embryos with small volume of medium in mircodrops was easier for manipulation and gave satisfactory results. In some trials we found that embryos began to cleave and form blastomeres as soon as culture conditions started (Fig.…”
Section: Resultsmentioning
confidence: 76%
“…; Brevini & Gandolfi ; Hall ; Shan et al . ). Organisms with a single copy of their genome provide a basis for genetic analyses where any recessive mutation of essential genes will show a clear phenotype due to the absence of a second gene copy (Carette et al .…”
Section: Introductionmentioning
confidence: 97%
“…Chromosome deletions and translocations have also been reported in the hPES-2 cell line, when cultivated for 120 passages [Mai et al, 2007]. Few cytogenetic data are available on mouse pESC lines, reporting a stable karyotype during culture (up to passage 120), analyzed by standard G-banding [Shao et al, 2007;Ju et al, 2008;Shan et al, 2012].…”
Section: Parthenogenetic Embryonic Stem Cellsmentioning
confidence: 99%
“…Our previous study indicated that the maternal expressed imprinting genes downregulated in aPgB (Shan et al . ). So we hypothesized that increasing the number of aggregated embryos might improve the development of parthenogenetic mice.…”
Section: Resultsmentioning
confidence: 97%
“…Meanwhile, the expression of maternal expressed imprinting genes such as H19, Gtl2, Igf2r decreased in aggregated blastocyst (Shan et al . ).…”
Section: Introductionmentioning
confidence: 97%